Identifying Components of Social Responsibility in Pharmaceutical Industry Companies: A Qualitative Study - Masume Bazrafshan; Hamidreza Vakilifard; Bizhan Abedini; Davood Khodadadi (Shiraz University of Medical Sciences, 2019)
Background: Social responsibility is a new topic in accounting literature that has been considered by researchers in various aspects. The purpose of this study was to identify the factors affecting social responsibility in pharmaceutical companies.   Methods: The present study was a qualitative content analysis research carried out in the year 2019. We performed an interview with 38 experts in the pharmaceutical industry to identify the factors affecting social responsibility in the pharmaceutical industry. In this study, the continuous comparison method of Strauss and Corbin (1998) was used to analyze the data.   Results: Based on the analysis, 25 categories and 7 main axes???? including environmental conditions; legal agents; and political, ethical, cultural, economic and social factors were identified as effective on social responsibility in pharmaceutical companies. Conclusion: Based on the findings of this study, it can be concluded that adherence to social responsibility by pharmaceutical companies is associated with optimal investment, producing a better quality product, more customer satisfaction, and cost reduction. Also, identifying the components of social responsibility in pharmaceutical companies can be effective in research on the afield of social responsibility.